Geophysical evidence for submarine methane seepage on the Western slope of Okinawa Trough - Luo, Di; Cai, Feng; Li, Qing; Yan, Guijing; Sun, Yunbao; Li, Ang; Dong, Gang (Frontiers in Earth Science, 2022)
Identifying seafloor methane seepage efficiently has important implications for assessing environmental impact, reducing the uncertainty of top seal integrity, understanding the petroleum system, and mitigating the drilling hazards due to shallow gas influx. Pore water geochemistry analyses suggest that the study area has an extremely high methane seepage flux and active methane anaerobic oxidation processes. However, geochemical data cannot provide details about the internal seepages. The geophysical dataset from the Western slope of Okinawa Trough, including 2D high-resolution seismic, sub-bottom profiles, and bathymetry, gives us a good opportunity to understand the detailed characteristics of methane seepages in this study. Geophysical data have revealed numerous methane seepage-related features such as seismic chimneys, pockmarks, submarine domes, and amplitude anomalies, including bright spots and enhanced reflections. Pockmarks and domes are often associated with seismic chimneys, indicating that fluid migration is important in their formation. The various geophysical expressions may represent different stages of methane seepage. Fluid quickly drains, causing severe sediment deformation and forming pockmarks, whereas domes may indicate the early stages of fluid discharge. Chimneys that do not extend to the seafloor may indicate that the venting is gradual and focused. Flares linked to domes or pockmarks may indicate that the fluid migration is active. Several factors triggered the existence of methane seepages on the Western slope of the Okinawa Trough, including tectonic setting, overpressure and rapid sedimentation.